Students’ Difficulties in Reading Comprehension at English for Food Technology - Putu Rusanti; Ni Kadek Ary Susandi; Ni Kadek Maya Cyntia Dewi; I Gusti Agung Galuh Wismadewi (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2023)
English for Food Technology (EFT) is one of the subjects which should be learnt in the third semester by students majoring Food and Technology Department. Most of the students find some difficulties in reading comprehension since they do not have background knowledge related to the new vocabularies. The purpose of this study was to describe the difficulties encountered by students in learning English for Food Technology especially in reading comprehension. This study employed qualitative design. There were 11 students who have passed English for Food Technology recruited as the sample of research. The data were collected by using questionnaire, test, and interview. The data were analyzed descriptively. The result of this research showed that students’ difficulties in learning English for Food Technology were unfamiliar words, lack of background knowledge, and complex syntax. It is expected that the lecturer give motivation and apply various teaching method so the students can be motivated in learning English for Food Technology.